CERAI BERSYARAT (SHIGHAT TA’LIQ) MENURUT DUAL SISTEM HUKUM (Hukum Islam dan Hukum Perdata) - Nurhadi Nurhadi (Media Keadilan: Jurnal Ilmu Hukum, 2020)
Marriage is a sacred covenant that unites two deeply bound human beings (mitsaqan ghalizha). The agreement was concluded in a consent agreement between guardian and future husband. Indonesian civil law requires saying the husband's sighat ta'liq to his wife. The essence of sighat ta'liq is conditional divorce between the two. Using normative (doctrinal) legal research, and comparative law approach (fiqh of comparative Mazhab). The results of the study explain that Islamic law assesses a legal marriage if enough conditions and harmony, without sighat ta'liq. Indonesian sighat ta'liq requirements are in government policy through the decree of the minister of religion number 3 of 1953. The aim of the sighat ta'liq is to protect the wife from the abuse of her husband, if the husband violates, the wife has the right to sue in a religious court (divorce). Lafadz sighat ta'liq was made referring to the regulation of the minister of religion number 2 of 1990, but the lafadz contained an understanding of "new marriage and a direct promise of divorce". Compilation of Islamic Law (KHI) as an enactment legislation explanation of UUP number 1 of 1974 Article 46 paragraph 3 does not require sighat ta'liqKeywords : conditional; divorce; dual law; shighat ta’liq; system.Pernikahan merupakan akad sakral yang menyatukan dua insan terikat kuat (mitsaqan ghalizha). Perjanjian disimpul dalam ijab kabul antara wali dan calon suami. Hukum perdata Indoesia mengharuskan mengucapkan sighat ta’liq suami kepada istrinya. Inti dari sighat ta’liq adalah perceraian bersyarat antara keduanya. Menggunakan penelitian hukum normatif (doktrinal), dengan pendekatan perbandingan hukum (fikih perbandingan mazhab). Hasil penelitian menjelaskan bahwa hukum Islam menilai pernikahan sah jika cukup syarat dan rukunnya, tanpa sighat ta’liq. Hukum di Indonesia kebersyaratan sighat ta’liq ada dalam kebijakan pemerintah melalui maklumat menteri agama nomor 3 tahun 1953. Tujuan adanya sighat ta’liq dalam rangka melindungi istri dari kesewenangan suami, jika suami melanggar, istri berhak menggugat ke pengadilan agama (cerai gugat). Lafadz sighat ta’liq dibuat mengacu pada peraturan menteri agama  nomor 2 tahun 1990, namun lafadz tersebut mengandung pemahaman “baru nikah langsung janji cerai”. Kompilasi Hukum Islam (KHI) sebagai peraturan perundangan penjelasan dari UUP nomor 1 tahun 1974 Pasal 46 ayat 3 tidak mewajibkan sighat ta’liq.Kata Kunci: bersyarat; bersyarat; dual sistem hukum; shighat ta’liq.